Inclusion In, and Exclusion From, Open Education Communities. Issue 2 (23rd December 2014) - Lane, Andy; Comas-Quinn, Anna; Thompson, Simon
This special issue is the fifth devoted to Open Educational Resources (OER) and the fourth to be drawn from papers presented at the annual UK-based OER conference. For this special issue, the editors selected papers from the OER14 conference, held in Newcastle in April 2014. The main conference theme was 'Building communities of open practice' with further themes on MOOCs and open courses; academic practice, development and pedagogy; open policy, research, scholarship and access; and students as users and co-creators. As open education matures it will be the communities we develop that make a difference to the success (or failure) of transforming education through openness. The five chosen papers in this special issue exemplify one facet of building communities of open practice – how people may, in theory and in practice, be included in or excluded from such communities despite the potential of the openness on offer.